Comparative functional analyses of PHR1, PHL1, and PHL4 transcription factors in regulating Arabidopsis responses to phosphate starvation - Wang, Zhen; Zheng, Zai; Liu, Dong (Frontiers in Plant Science, 2024)
To cope with phosphate (Pi) starvation, plants trigger an array of adaptive responses to sustain their growth and development. These responses are largely controlled at transcriptional levels. In Arabidopsis (Arabidopsis thaliana), PHOSPHATE RESPONSE 1 (PHR1) is a key regulator of plant physiological and transcriptional responses to Pi starvation. PHR1 belongs to a MYB-CC-type transcription factor family which contains 15 members. In this PHR1 family, PHR1/PHR1-like 1(PHL1) and PHL2/PHL3 form two distinct modules in regulating plant development and transcriptional responses to Pi starvation. PHL4 is the most closely related member to PHR1. Previously, using the phr1phl4 mutant, we showed that PHL4 is also involved in regulating plant Pi responses. However, the precise roles of PHL1 and PHL4 in regulating plant Pi responses and their functional relationships with PHR1 have not been clearly defined. In this work, we further used the phl1phl4 and phr1phl1phl4 mutants to perform comparative phenotypic and transcriptomic analyses with phr1, phr1phl1, and phr1phl4. The results showed that both PHL1 and PHL4 act redundantly and equally with PHR1 to regulate leaf senescence, Pi starvation induced-inhibition of primary root growth, and accumulation of anthocyanins in shoots. Unlike PHR1 and PHL1, however, the role of PHL4 in maintaining Pi homeostasis is negligible. In regulating transcriptional responses to Pi starvation at genomic levels, both PHL1 and PHL4 play minor roles when acts alone, however, they act synergistically with PHR1.In regulating Pi starvation-responsive genes, PHL4 also function less than PHL1 in terms of the number of the genes it regulates and the magnitude of gene transcription it affects. Furthermore, no synergistic interaction was found between PHL1 and PHL4 in regulating plant response to Pi starvation. Therefore, our results clarified the roles of PHL1 and PHL4 in regulating plant responses to Pi starvation. In addition, this work revealed a new function of these three transcription factors in regulating flowering time.